Multistage inhibitors of the malaria parasite: Emerging hope for chemoprotection and malaria eradication. Issue 5 (26th January 2018) - Poonam; Gupta, Yash; Gupta, Nikesh; Singh, Snigdha; Wu, Lidong; Chhikara, Bhupender Singh; Rawat, Manmeet; Rathi, Brijesh
Abstract: Over time, several exciting advances have been made in the treatment and prevention of malaria; however, this devastating disease continues to be a major global health problem and affects millions of people every year. Notably, the paucity of new efficient drug molecules and the inevitable drug resistance of the malaria parasite, Plasmodium falciparum, against frontline therapeutics are the foremost struggles facing malaria eradication initiatives. According to the malaria eradication agenda, the discovery of new chemical entities that can destroy the parasite at the liver stage, the asexual blood stage, the gametocyte stage, and the insect ookinete stage of the parasite life cycle (i.e., compounds exhibiting multistage activity) are in high demand, preferably with novel and multiple modes of action. Phenotypic screening of chemical libraries against the malaria parasite is certainly a crucial step toward overcoming these crises. In the last few years, various research groups, including industrial research laboratories, have performed large‐scale phenotypic screenings that have identified a wealth of chemical entities active against multiple life stages of the malaria parasite. Vital scientific and technological developments have led to the discovery of multistage inhibitors of the malaria parasite; these compounds, considered highly valuable starting points for subsequent drug discovery and eradication of malaria, are reviewed.